A Jew's best friend? : the image of the dog throughout Jewish history - Lieberman, Phillip I., 1970-; Zalashik, Rakefet, 1973- (Sussex Academic Press, 2013)
A discussion on the specific cultural manifestations of the relationship between dogs and Jews, from ancient times to the present, this work covers a geographical range extending from the Middle East through Europe and to North America, while the contributorsall of whom are senior university scholars specializing in various disciplinesprovide a unique cross-cultural, trans-national, diachronic perspective. An important theme is the constant tension between domination/control and partnership that underpins the relationship of humans to animals, as well as the connection between Jewish societies and their broader host cultures. A public increasingly interested in cultural history in general and Jewish history in particular will benefit from the diverse perspectives provided herein.